MLS711: Organization of Knowledge - UiTM, College of Computing, Informatics and Mathematics (2023)
The course examines theories and practices in knowledge organization: cataloguing, bibliographic description, subject analysis and classification. It covers the organization of information in various formats, including examination and application of the Anglo-American Cataloging Rules (AACR, 2nd revised ed.), major classification schemes and subject headings lists, authority work and formatting bibliographic or surrogate records for computer manipulation using international standards like MARC and Dublin Core.